Implementation of Al-Ghazali's Educational Perspective in Modern Islamic Educational Institution - Rahman, Habibur; Anam, Rijal Khoirul; Aji, Handaru Baskara; Kurniawan, Ilham (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study explores the application of Al-Ghazali's educational concepts in the contemporary education system at a modern Islamic Educational Institution. Using a qualitative approach with a case study design, this study seeks to gain an in-depth understanding of implementing Al-Ghazali's values. Data were collected through in-depth interviews with four teaching staff and two administrative staff and analyzed using thematic analysis methods. The results indicate that the institution where the study was conducted has successfully integrated moral values into its curriculum, using teaching methods focusing on understanding and reflection and implementing a strong spiritual development program. Teachers act as role models and spiritual guides, which aligns with Al-Ghazali's view of the importance of holistic education, which includes moral, intellectual, and spiritual aspects. This study's conclusion shows that applying Al-Ghazali's educational concepts has significantly contributed to improving the quality of modern Islamic education through a holistic approach that integrates moral, intellectual, and spiritual aspects. The findings also offer a value-based education model that can be adapted by various Islamic educational institutions in the future.